2001
DOI: 10.1055/s-0037-1612658
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in Young Adults: The Role of Paradoxical Embolism

Abstract: SummaryStroke in young adults may be devastating and frequently no cause can be found. However, there is ample literature to suggest an association between cryptogenic stroke in young people and paradoxical embolisation via a venous to arterial circulation shunt (v-aCS), commonly due to patent foramen ovale (PFO). Although paradoxical embolisation is assumed to be a rare event, this review suggests that it is an important or even dominant cause of stroke in young people and that a transcranial Doppler (TCD) te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 78 publications
(75 reference statements)
1
34
0
1
Order By: Relevance
“…29 However, sparse reports suggest that this pathomechanism has probably been underestimated. 30 Recently, Cramer and coworkers 31 diagnosed paradoxical embolism in 29% of patients in a small series of subjects with cryptogenic stroke and suggested that deep-vein thrombosis may be missed in a significant proportion of cases if an extensive study of pelvic and calf vein is not performed, in addition to the routine popliteal and femoral veins investigation. The Paradoxical Embolism From Large Veins in Ischemic Stroke (PELVIS) study is ongoing to address these preliminary observations.…”
Section: Discussionmentioning
confidence: 99%
“…29 However, sparse reports suggest that this pathomechanism has probably been underestimated. 30 Recently, Cramer and coworkers 31 diagnosed paradoxical embolism in 29% of patients in a small series of subjects with cryptogenic stroke and suggested that deep-vein thrombosis may be missed in a significant proportion of cases if an extensive study of pelvic and calf vein is not performed, in addition to the routine popliteal and femoral veins investigation. The Paradoxical Embolism From Large Veins in Ischemic Stroke (PELVIS) study is ongoing to address these preliminary observations.…”
Section: Discussionmentioning
confidence: 99%
“…Also, we do not know what is the optimal strategy for secondary stroke prevention in patients with cryptogenic stroke and PFO, and whether those with a coagulation abnormality should be treated differently. The current therapeutic options for patients with PFO vary from antiplatelet or anticoagulant therapy to surgical or transcatheter closure of the PFO [3,33]. One recent study suggested that those patients with both PFO and ASA who have had a cryptogenic stroke constitute a subgroup with a higher risk of recurrent stroke [34], but another recent study could not confirm this finding [35].…”
Section: Discussionmentioning
confidence: 99%
“…In patients 55 years of age or younger with cryptogenic brain infarction, patent foramen ovale (PFO) has been shown to be a more common finding (56%) than in controls (18%) and in patients with brain infarction of determined cause (17%), suggesting paradoxical embolism as the mechanism for stroke [2,3]. Assuming that strokes are due to paradoxical embolism in the presence of PFO, a high incidence of deep venous thrombosis (DVT) or a high frequency of either inherited or acquired conditions leading to an increased incidence of venous thromboembolism would be expected in this group of patients [3]. However, as a venous source of paradoxical emboli is seldom identified in patients with PFO and cerebral ischaemia [4], paradoxical embolism is often only assumed.…”
Section: Introductionmentioning
confidence: 99%
“…S tudies of cryptogenic stroke in young patients have shown that the incidence of patent foramen ovale (PFO) is higher than in patients with established causes of stroke. [1][2][3][4][5] The suggested mechanism for a cerebrovascular event in patients with a PFO is based on a transient increase in right heart pressure, which would cause a transient right-to-left shunt through the PFO, with the possibility that a venous embolus could cross the PFO and embolize the cerebral circulation (paradoxical embolism). Paradoxical emboli could also reach other vascular beds, such as the coronary arteries, and cause acute myocardial infarction (MI).…”
mentioning
confidence: 99%